Heatstroke during endurance exercise: Is there evidence for excessive endothermy? - Rae, D. E.; Knobel, G. J.; Mann, T.; Swart, J.; Tucker, R.; Noakes, T. D. (Medicine & Science in Sports & Exercise, 2008)
Purpose: Five of 28,753 cyclists participating in an annual 109-km bicycle race died, four within 24 h of the race and the fifth 17 d later. All five deaths were reported to be the consequence of exertional heatstroke. One runner of 6874 participating in an annual 56-km ultramarathon developed heatstroke and required active cooling for 10 h to achieve normothermia. The purpose of this article was to postulate (i) why only 6 of 35,627 athletes were hospitalized for heatstroke in these races, (ii) if exercise alone could have elevated their body temperatures sufficiently to cause heatstroke, and (iii) why the runner required such prolonged cooling.